PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PRODUK DONAT MADU (Studi Pada Konsumen CV. Donat Madu Cihanjuang–Pekanbaru) - Tias Windarti; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine how much influence product quality and service quality to consumer satisfaction. Samples in this study were taken as many as 99 respondents and techniques used Non-probability sampling with Accidental Sampling approach. Data in this study using survey method through questionnaires filled by consumers. Data were obtained by using multiple regression analysis. This analysis includes Validity Test, Reliability Test, Multiple Regression Analysis, Hypothesis Testing through t Test and F Test, and Coefficient Determination analysis (R2). Variable product quality has a greater influence on consumer buying interest that is equal to 0.234 and service quality variable has an effect of 0.143. Hypothesis testing using t test showed that the independent variables studied were product quality and service quality proved to have a positive and significant effect on the dependent variable of consumer satisfaction. Then the results of analysis using the F test can be seen that product quality and service quality together significant effect on consumer satisfaction. The coefficient of determination (R2) indicates that contribution of product quality and service quality influence to consumer satisfaction 56.1%. While remaining 43.1% influenced by other variables that are not included in this regression model.Keywords: Product Quality, Service Quality, and Consumer Satisfaction